Cost of fruiting, size regulation, and senescence in a long-lived geophyte - James D. Thomson; David F. Andrews (PLoS ONE, 2026)
Grown in a transplant garden that provides field conditions but prevents predation by pocket gophers, plants of Erythronium grandiflorum (Liliaceae) have been exhumed annually (as dormant corms), photographed, and weighed over 33 years. From seed, plants grow to flowering size in about 5–6 years. They subsequently regulate their size by occasional vegetative splitting and by flowering and fruiting; producing one fruit costs a plant about 8% of the weight it would have gained if it had not flowered. Death is rare: a few plants have gradually lost weight and died in a way consistent with classical senescence, but others have died suddenly from fungal infection after previously growing robustly. Additional years of observation will be needed to clarify the issue of senescence. The data are archived and future collaborators are sought.